Cardiac Troponin and Tropomyosin: Structural and Cellular Perspectives to Unveil the Hypertrophic Cardiomyopathy Phenotype - Marques, Mayra de A.; de Oliveira, Guilherme A. P. (Frontiers in Physiology, 2016)
Inherited myopathies affect both skeletal and cardiac muscle and are commonly associated with genetic dysfunctions, leading to the production of anomalous proteins. In cardiomyopathies, mutations frequently occur in sarcomeric genes, but the cause-effect scenario between genetic alterations and pathological processes remains elusive. Hypertrophic cardiomyopathy (HCM) was the first cardiac disease associated with a genetic background. Since the discovery of the first mutation in the β-myosin heavy chain, more than 1400 new mutations in 11 sarcomeric genes have been reported, awarding HCM the title of the “disease of the sarcomere.” The most common macroscopic phenotypes are left ventricle and interventricular septal thickening, but because the clinical profile of this disease is quite heterogeneous, these phenotypes are not suitable for an accurate diagnosis. The development of genomic approaches for clinical investigation allows for diagnostic progress and understanding at the molecular level. Meanwhile, the lack of accurate in vivo models to better comprehend the cellular events triggered by this pathology has become a challenge. Notwithstanding, the imbalance of Ca2+ concentrations, altered signaling pathways, induction of apoptotic factors, and heart remodeling leading to abnormal anatomy have already been reported. Of note, a misbalance of signaling biomolecules, such as kinases and tumor suppressors (e.g., Akt and p53), seems to participate in apoptotic and fibrotic events. In HCM, structural and cellular information about defective sarcomeric proteins and their altered interactome is emerging but still represents a bottleneck for developing new concepts in basic research and for future therapeutic interventions. This review focuses on the structural and cellular alterations triggered by HCM-causing mutations in troponin and tropomyosin proteins and how structural biology can aid in the discovery of new platforms for therapeutics. We highlight the importance of a better understanding of allosteric communications within these thin-filament proteins to decipher the HCM pathological state.